Self-Reward and Gender Disparity on TikTok: A Comparative Content Analysis Study of Generation Z Behavior and Motives - Reva Akhila Fiandari; Orchida Azzahrra Putri Hidayah; Mahesta Dwi Oktaviana; Nurlita Dwi Amara; Harlinda Zahra Kamila; Naysilla Aisyah Putri Nurfazila; Dimas Kurnia Nurfathoni; Nanang Martono (Universitas Tribhuwana Tungga Dewi, 2026)
The phenomenon of self-reward on social media has transformed into an integral part of Generation Z's lifestyle, which frequently interconnects with flexing behavior. This study aims to compare the patterns of self-reward content between male and female users on the TikTok platform by examining the simultaneous relationship between sex, action motives, and the characteristics of cyber-audience comment responses. Employing a quantitative approach, this research applies manifest and latent content analysis methods to 297 content units extracted using a hashtag-based simple random sampling technique. The descriptive analysis proves that self-reward activities are massively dominated by the female group (74.1%) compared to the male group (25.9%). Females tend to manifest forms of self-reward through the commodification of goods driven by emotional regulation motives (mood enhancement). Conversely, males are more oriented toward recreational and culinary aspects driven by objective performance achievement motives. Generally, public sentiment in the comment section is dominated by positive responses. The Chi-Square test results confirm that the disparity in comment responses based on the creator's sex variable is not statistically significant (p0,05). These empirical findings confirm the relevance of Gender Role Theory, demonstrating that differences in the articulation of self-expression in digital spaces reflect the conditioning of sociocultural gender norms.Fenomena self-reward di media sosial telah bertransformasi menjadi bagian integral dari gaya hidup Generasi Z yang kerap berinterkoneksi dengan perilaku flexing. Penelitian ini bertujuan untuk mengomparasi pola konten self-reward antara pengguna laki-laki dan perempuan di platform TikTok dengan menguji hubungan simultan antara jenis kelamin, motif tindakan, dan karakteristik respons komentar khalayak siber. Melalui pendekatan kuantitatif, riset ini menerapkan metode analisis isi manifest dan laten terhadap 297 unit konten yang diekstraksi menggunakan teknik simple random sampling berbasis tagar. Hasil analisis deskriptif membuktikan bahwa aktivitas self-reward didominasi secara masif oleh kelompok perempuan (74,1%) dibandingkan laki-laki (25,9%). Perempuan cenderung memanifestasikan bentuk self-reward melalui komodifikasi barang atas dasar motif regulasi emosional (mood enhancement). Sebaliknya, laki-laki lebih berorientasi pada aspek rekreasi dan kuliner yang didorong oleh motif capaian performa objektif. Secara umum, sentimen publik di kolom komentar didominasi oleh respons positif. Hasil uji Chi-Square mengonfirmasi bahwa disparitas respons komentar berdasarkan variabel jenis kelamin kreator tidak signifikan secara statistik (p0,05). Temuan empiris ini mengukuhkan relevansi Gender Role Theory bahwa perbedaan artikulasi ekspresi diri di ruang digital merupakan refleksi dari pendisiplinan norma gender sosiokultural.